Non-monotonic behavior of weak-polyelectrolytes adsorption on a cationic surface: A Monte Carlo simulation study. (6th January 2021) - Narambuena, Claudio F.; Blanco, Pablo M.; Rodriguez, Adrian; Rodriguez, Diego E.; Madurga, Sergio; Garcés, José L.; Mas, Francesc
Abstract: In this work, the weak polyelectrolyte (PE) adsorption on a strong cationic surface is studied with constant pH Monte Carlo simulations using a coarse-grained model. When a large number of PE chains is added to the system, the PE adsorbed amount vs pH curve exhibits a non-monotonic behavior, with the appearance of a maximum close to the intrinsic p K a 0 -value of the PE titratable groups. The apparent p K a -value of the PE chains shows a non-trivial tendency depending on the pH-value and the surface coverage degree. In increasing the pH-value, the small anions that accompany the cationic surface are replaced by PE chains and small cations. For pH > p K a 0 + 1, an evident charge reversion of surface is observed. These results are explained analyzing the interplay between the attractive and repulsion electrostatic interactions between the different components of the system (inter- and intra-charged monomers of PE chains, the strong cationic surface and small ions) and their effects on the PE chain ionization. Graphical abstract: Image 1 Highlights: Weak polyelectrolyte adsorption on a strong cationic surface is studied using constant pH Monte Carlo simulation. The adsorbed amount vs pH shows a maximum value close to the intrinsic p K a -value of the titratable groups of the PE. The apparent p K a -value vs pH of the adsorbed PE chains exhibits a nontrivial behavior as a function of the coverage degree. Charge reversion is obtained at pH-values beyond the intrinsic p K a -value of the polyelectrolyte titratable groups.